FT IR and FT Raman Spectral Investigations of Anatolian Attapulgite and its Interaction with4 4 Bipyridyl - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 1995)
The adsorption of 4,4′-bipyridyl by natural attapulgite from Anatolia (Turkey) has been studied using vibrational spectroscopy. Investigations of Fourier-transform infrared and Fourier-transform Raman spectra of adsorbed 4,4′-bipyridyl indicate the presence of physical and chemical sorbed surface species. No anionic surface species has been observed. It is proposed that chemisorbed 4,4′-bipyridyl molecules are coordinated to either Lewis acidic centers or surface hydroxyls as monodentate ligands.